Study of the efficiency of ZnAl2O4 as green nanocatalyst - Birhi, Damiana Nofita; Laka, Antonia Fransiska (Univeritas Papua, 2024)
Waste from chemical reactions is still a hot issue to be discussed today. Green chemistry in its concept offers catalysts as an alternative to reducing waste resulting from chemical reactions. This literature study aims to examine the method of making ZnAl2O4 nanocatalysts and doping materials that are more effective in various reactions by considering the advantages and disadvantages of each. The content of the study includes the ZnAl2O4 nanocatalyst synthesis method, combination catalyst, and catalytic effectiveness in chemical reactions. Combustion, sol-gel, co-precipitation, hydrothermal, and microwave are the most common methods in the synthesis of ZnAl2O4. The use of precursors, fuel, and precipitating agents are very important factors when using combustion, sol-gel, and co-precipitation methods. Other factors that need to be considered are the raw material ratio, pH, and calcination temperature. The pH of the solution is 6-9 and the calcination temperature of 600oC – 800oC is the ideal point for producing nanocatalyst. The calcination temperature is lower to 300oC – 500oC when using hydrothermal and microwave as a synthesis method. ZnAl2O4 nanocatalyst has been identified as having good catalytic activity, but not higher than ZnAl2O4 combined with other catalysts. The combination of a catalyst with ZnAl2O4 spinel in hydrogenation, dehydrogenation, esterification, degradation, and organic synthesis has high catalytic activity with a conversion rate and selectivity of >70%.